Extended Descriptions and Revised Diagnoses of Three Recently Described, Little-Known Mountain Dragons (Reptilia: Agamidae: Diploderma) from the Yalong River Valley in Southwest China - Dong, Wenjie; Li, Ling; Xun, Hao; Gao, Wei; Wang, Kai; Che, Jing (Zootaxa, 2024)
Mountain Dragons of the genus Diploderma has experienced rapid taxonomic change in the recent years. The fast rate of taxonomic changes often leads to insufficient data for newly described species on their morphological variation, especially regarding sexual dimorphism, as well as the missing information on their natural history and conservation status. Limited time for taxonomic works may also result in misidentification of “new species”. Among these recently described species, two taxa from the Yalong River Valley in Southwest China, namely D. panchi Wang, Zheng, Xie, Che, Siler, 2021 and D. panlong Wang, Che, Siler, 2021, are only known from specimens of a single sex; and D. bowoense Wang, Gao, Wu, Siler, Che, 2022 is known from a very limited number of specimens only. As extreme sexual dimorphism and dichromatism are evident in the genus, and since many other new species have been described ever since and only compared to the available materials at the time, it is crucial to fill the gap of knowledge and revise the diagnoses of D. panchi, D. panlong, and D. bowoense based on more specimens of both sexes accordingly. We provide expanded descriptions of D. panchi, D. panlong and D. bowoense based on newly collected topotypic specimens, and fill the gaps of the sexual dimorphism of D. panchi and D. panlong. In addition, we discussed the validity of a more recently described species, D. kangdingense, with regards to D. bowoense. Finally, we reemphasized the importance of stabilizing Chinese common names of Diploderma and provide Chinese common names for the recently described species.